Fetal ultrasonography of Chiari II malformation - Sambhav, Kumar; Dushyant, Kumar; Jayaswal, Shailza R. (International Journal of Research in Medical Sciences, 2024)
Chiari II malformation is a complex hindbrain malformation, embryologically presenting as a neural tube closure defect comprising of downward herniation of cerebellum, pons, medulla and fourth ventricle into the spinal canal. We present a case of Chiari II malformation depicting essential sonographic observations at 20 weeks of gestation. Such fetuses have high morbidity and mortality and early diagnosis of such a disease is essential in terms of planning including pregnancy termination or neurosurgical procedures for follow-up pregnancy. Ultrasonography is an indispensable modality for the evaluation of fetal anatomy, growth, and such congenital anomalies.